A Psycholinguistic Analysis of Students Problems in Communicating Using English - Elsa Margaretha Gultom; Jamaluddin Nasution; Lisa Septia Dewi Br. Ginting (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study investigates the psycholinguistic factors that influence junior high school students' ability to communicate in English, focusing on emotional and cognitive barriers that impede speaking performance. While numerous studies have examined speaking difficulties among university students, research on younger learners particularly junior high school students remains limited. This study addresses that gap by exploring the challenges faced by seventh-grade students at SMP Nasrani 5 Medan. Employing a descriptive qualitative design, data were collected through classroom observations and in-depth interviews with selected students and teachers. The findings reveal that affective factors, such as fear of making mistakes, embarrassment, and anxiety, are the most dominant barriers to speaking English. Additional obstacles include overreliance on internal monitoring of grammar, limited vocabulary, and insufficient sentence construction skills. The study also highlights the importance of a supportive learning environment: strategies such as relaxed classroom settings, the use of engaging media like songs, and teacher encouragement were found to reduce psychological resistance and enhance students’ willingness to speak. These insights have practical implications for English language teaching, particularly in developing approaches that address emotional as well as linguistic challenges in early-stage language learners.